Self-compassion sebagai Prediktor Psychological Well-being Mahasiswa di Tiga Perguruan Tinggi Negeri Kota Malang - Malinda Syafrina; Ika Andrini Farida (Universitas Negeri Malang, 2023)
Psychological well-being is a positive evaluation of oneself that is derived from oneself and others, the ability to direct themselves and their environment, a feeling of growth and development, the ability to interpret life, and the ability to associate well with others. One of the factors that can improve psychological well-being is self-compassion. The purpose of this study was to determine the predictive relationship between self-compassion and the psychological well-being of students at three public universities in Malang. This study used quantitative research methods and accidental sampling techniques. The research sample was 250 students from Universitas Negeri Malang, Universitas Brawijaya, and UIN Maulana Malik Ibrahim. The research instrument used was the self-compassion scale to measure self-compassion and the Indonesian version of the psychological well-being scale to measure psychological well-being. The data analysis technique used is simple linear regression analysis. The results of the study show that self-compassion predicts psychological well-being. The result of R Square= 0.548 means that the self-compassion component contributes 54.8% to psychological well-being. Based on the results found, self-compassion can be a predictor in improving the psychological well-being of students at three public universities in Malang. AbstrakPsychological well-being adalah evaluasi positif yang dilakukan untuk diri sendiri dan orang lain, kemampuan mengarahkan diri dan lingkungannya, perasaan tumbuh dan berkembang, kemampuan menginterpretasikan kehidupan, dan kemampuan bergaul dengan baik dengan orang lain. Salah satu faktor yang dapat meningkatkan psychological well-being adalah self-compassion. Tujuan dari penelitian ini adalah untuk mengetahui hubungan prediktif antara self-compassion dan psychological well-being mahasiswa di tiga perguruan tinggi negeri di Kota Malang. Penelitian ini menggunakan metode penelitian kuantitatif dan teknik pengambilan sampel accidental sampling. Sampel penelitian adalah 250 mahasiswa dari Universitas Negeri Malang, Universitas Brawijaya, dan UIN Maulana Malik Ibrahim. Instrumen penelitian yang digunakan adalah skala welas diri untuk mengukur self-compassion dan skala psychological well-being versi Indonesia untuk mengukur kesejahteraan psikologis. Teknik analisis data yang digunakan adalah analisis regresi linier sederhana. Hasil penelitian menunjukkan self-compassion memprediksi kesejahteraan psikologis. Hasil R Square=0,548 artinya komponen self-compassion berkontribusi sebesar 54,8% terhadap kesejahteraan psikologis. Berdasarkan hasil yang ditemukan, self-compassion dapat menjadi prediktor dalam meningkatkan kesejahteraan psikologis mahasiswa di tiga perguruan tinggi negeri di Kota Malang.